2018
DOI: 10.15353/joci.v14i1.3402
|View full text |Cite
|
Sign up to set email alerts
|

60+ Online:

Abstract: Seniors are amongst the most digitally excluded in Australia. Despite the increasing popularity of social media, seniors often lack access to technology and to basic digital skills. Thus many seniors do not derive the social benefits and service realisation that arise from online forms of communication and engagement. One barrier to digital inclusion for seniors is learning how to make use of digital and online tools in a way that incorporates their specific needs, interests and capabilities. The 60+ Onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…The selection of learning content should be based on the needs of the learners, address specific everyday problems as well as life circumstances, and take social processes into account [ 1 , 3 , 11 , 14 , 19 , 27 , 40 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. This can be done by involving them in the participative development process itself.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selection of learning content should be based on the needs of the learners, address specific everyday problems as well as life circumstances, and take social processes into account [ 1 , 3 , 11 , 14 , 19 , 27 , 40 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. This can be done by involving them in the participative development process itself.…”
Section: Resultsmentioning
confidence: 99%
“…This can be done by involving them in the participative development process itself. To realize this, needs assessment or co-creative workshops can be identified in which the content of the curriculum is discussed and debated with the target group in advance [ 1 , 27 , 40 , 47 , 48 , 50 , 52 , 53 , 54 ]. Barrie et al (2021) identify the direct involvement of older people as key to creating a positive learning environment and confronting ageism [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in relation to older people and digitisation has focused on digital exclusion and the ability of older people to learn media skills and communicate effectively and confidently. Studies have been conducted to examine what interventions can be used to increase elderly online participation (Davis et al, 2018; Poscia et al, 2018). Jones et al (2015) found the use of volunteers to train older citizens in how to use the Internet led to an increase in social contact for the participants.…”
Section: Introductionmentioning
confidence: 99%
“…Approaches that are able to address the specific needs of local communities with sufficient participant buy-in (Baker et al ., 2017), as in the adoption of ‘living lab’ models, have been highly successful (Hughes et al ., 2018). Also with older adults, there is strong evidence to show the importance of taking an interests-based approach to skills, literacies and digital participation (Beh et al ., 2018; Davis et al ., 2018), as well as adopting a ‘blended’ approach (both in-person and online learning) to digital literacy workshops (Martínez-Alcalá et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%